2016
DOI: 10.1074/jbc.m116.715599
|View full text |Cite
|
Sign up to set email alerts
|

Synaptogyrin-2 Promotes Replication of a Novel Tick-borne Bunyavirus through Interacting with Viral Nonstructural Protein NSs

Abstract: Synaptogyrin-2 is a non-neuronal member of the synaptogyrin family involved in synaptic vesicle biogenesis and trafficking. Little is known about the function of synaptogyrin-2. Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease characterized by high fever, thrombocytopenia, and leukocytopenia with high mortality, caused by a novel tick-borne phlebovirus in the family Bunyaviridae. Our previous studies have shown that the viral nonstructural protein NSs forms inclusion bodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 59 publications
0
26
0
1
Order By: Relevance
“…Further support that cellugyrin may exist in cytoplasmic vesicles comes from Chapel et al ( 2013 ) who have suggested that this cellular protein is a lysosomal transporter protein. Of particular importance to our study is a recent report by Sun et al ( 2016 ) who were studying Bunyavirus infection in mammalian cells and demonstrated that synaptogyrin-2 (cellugyrin) interacts with viral nonstructural proteins and together were transported into inclusion bodies “reconstructed from lipid droplets” during infection. They further reported that this translocation was critical to viral replication as silencing of cellugyrin expression reduced inclusion body formation and decreased virus titers.…”
Section: Discussionmentioning
confidence: 99%
“…Further support that cellugyrin may exist in cytoplasmic vesicles comes from Chapel et al ( 2013 ) who have suggested that this cellular protein is a lysosomal transporter protein. Of particular importance to our study is a recent report by Sun et al ( 2016 ) who were studying Bunyavirus infection in mammalian cells and demonstrated that synaptogyrin-2 (cellugyrin) interacts with viral nonstructural proteins and together were transported into inclusion bodies “reconstructed from lipid droplets” during infection. They further reported that this translocation was critical to viral replication as silencing of cellugyrin expression reduced inclusion body formation and decreased virus titers.…”
Section: Discussionmentioning
confidence: 99%
“…There are indications that a range of other viruses may also exploit LDs for virus maturation. LD-association has been reported for non-structural proteins of orbiviruses [147], bovine viral diarrhea virus [148], and bunyavirus [149, 150], but the functional significance of this LD localization remains to be investigated.…”
Section: 1 Protein Maturationmentioning
confidence: 99%
“…We conclude that the induction of the IRF3 and IRF7 transcripts varied greatly among the tested cell types, with the HepG2 cells to be the most potent for induction. HepG2, originated from human liver epithelial cells, could be unique in response to SFTSV infection as we know that the liver is one of the severely affected organs during SFTSV infection (30).…”
Section: Induction Of Irf7 and Other Immune Components In Cells Infecmentioning
confidence: 99%